Determination Of Frequency Dependent Global Dynamic Properties Of Engine Mount - Ooi, Lu Ean (2014)
The dynamic properties of engine mount influence the performance of the engine mounting system. The frequency-dependent properties represented the more accurate properties of the engine mount as opposed to the frequency-independent properties model. Sifat dinamik pelapik getah enjin mempengaruhi prestasi untuk pelapik getah enjin. Sifat kekakuan dan faktor kehilangan bersandarkan frekuensi menerangkan sifat pelapik enjin dengan lebih tepat berbanding model yang menggunakan sifat redaman tak bersandar frekuensi.